1989
DOI: 10.1007/bf02821296
|View full text |Cite
|
Sign up to set email alerts
|

Effect of γ-irradiation on F-2 and T-2 toxin production in corn and rice

Abstract: Fusarium graminearum and F. tricinctum were grown on moistened corn and rice. After inoculation the substrates were exposed to gamma-irradiation and growth rate together with mycotoxin production were measured. A delay in mycelium growth and an increase in F-2 and T-2 toxin production occurred after irradiation with 1 and 3 kGy. The maximum F-2 production was 10.7 mg/kg on rice at 3 kGy, whereas T-2 was 735 micrograms/kg on rice at 3 kGy. At 9 kGy neither growth nor toxin production could be detected in any in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
2

Year Published

1991
1991
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 7 publications
0
4
2
Order By: Relevance
“…Though it has been reported that some common fungi like Alternaria, Fusarium, Curvularia have shown resistance to gamma (0.6-1.7 Mrad) from Cs-137 (Saleh et al, 1988), our present data show the potential of gamma exposure of 1-6 kGy from 60 Co source to induce significant depletion of seed infecting fungal colony. In contrast to the findings of Halasz et al (1989) and Aziz et al (1997) data of our present investigation show efficiency of gamma exposure in controlling Fusarium sp at a much lower exposure of 1 kGy. Findings of some earlier workers has documented effectiveness of gamma in controlling fungal flora on black peeper (Emam et al, 1995), fruit samples like plum, pears and apples (Gherbawy, 1998), and black cumin (Nigella sativa) (Zeinab et al, 2000).…”
Section: Frequency Of Fungal Colonycontrasting
confidence: 85%
See 1 more Smart Citation
“…Though it has been reported that some common fungi like Alternaria, Fusarium, Curvularia have shown resistance to gamma (0.6-1.7 Mrad) from Cs-137 (Saleh et al, 1988), our present data show the potential of gamma exposure of 1-6 kGy from 60 Co source to induce significant depletion of seed infecting fungal colony. In contrast to the findings of Halasz et al (1989) and Aziz et al (1997) data of our present investigation show efficiency of gamma exposure in controlling Fusarium sp at a much lower exposure of 1 kGy. Findings of some earlier workers has documented effectiveness of gamma in controlling fungal flora on black peeper (Emam et al, 1995), fruit samples like plum, pears and apples (Gherbawy, 1998), and black cumin (Nigella sativa) (Zeinab et al, 2000).…”
Section: Frequency Of Fungal Colonycontrasting
confidence: 85%
“…Such differential response has been reported earlier in case of Fusarium sp. (Halasz et al, 1989;Ramakrishana et al, 1991;Aziz et al, 1997) and Aspergillus sp. (Emam et al, 1995;EL-Bazza et al, 2001) in association with different infected hosts.…”
Section: Frequency Of Fungal Colonymentioning
confidence: 99%
“…Our present data show the potential of gamma exposure of 2-3 kGy from 60 Co source to induce significant depletion of seed-infecting fungal colony. In contrast to the findings of Halasz et al (1989) and Aziz et al (1997), data of our present investigation show efficiency of gamma exposure in controlling fungi at a lower dose. Also, such differential response has been reported earlier in the case of Aspergillus sp.…”
Section: Effects Of Gamma Irradiation On Seed-infecting Fungicontrasting
confidence: 85%
“…Other studies have shown that microwaves and ozone can be effective in reducing their toxicity (Farag, Rashed, and Abo Hggr, 1996; Chatterjee and Mukherjee 1993). Gamma-irradiation has also been employed for mycotoxin inactivation, although there have been mixed results using this technique (Wilson et al 2004; Aziz, Attia, and Farag 1997; Halasz et al 1989). One study showed that superactivated charcoal can neutralize T-2 toxin (Fricke and Jorge 1990).…”
Section: Discussionmentioning
confidence: 99%